1022 Early Cholecystectomy in the Ageing Population. (19th August 2022) - Sturges, P; Gupta, A; Rashid, U; Rupasinghe, SN; Adjepong, S; Parampalli, U; Kirby, GC; Jain, RK; Rink, J; Riera-Portell, M; Pattar, J
Abstract: Background: The age group of patients presenting acutely with biliary pathology is rising and gallstone disease can no longer be said to be a disease of the young. The World Health Organisation classifies those aged 65 and over as elderly. Early cholecystectomy is accepted as a safe and effective method of managing acute biliary pathology, reducing further admissions, and reducing in-hospital stays. Our unit does not use age as barrier but uses performance status and co-morbidity to identify potential candidates for cholecystectomy. Method: Patients over the age of 65 who underwent acute cholecystectomy (AC) via the emergency cholecystectomy lists, were audited from 31st December 2019 to 31st June 2021. Patient demographics, co-morbidities and surgical factors were recorded. The primary outcome measures were in-hospital stay and re-admission, secondary outcomes were complications and perioperative mortality. Results: 41 elderly patients underwent AC during the audit period, (Female 56%, Male 44%). 30 patients had acute cholecystitis (73%). The median inpatient stay following surgery was 2 days (range 2–5 days) and the median admission to surgery time was 6 days (range 5–12 days). Three patients had a subtotal cholecystectomy. There were 3 complications from surgery which were all between a Clavien-Dindo score of 2 and 3. There were 3 immediate post-operative readmissions, with one 30-day mortality from ERCP pancreatitis and not from the operation. Conclusion: Early cholecystectomy appears to be a safe and effective treatment for this group of patients and based on this evidence we should continue to offer this treatment to patients irrespective of age.